PERINATAL OUTCOMES OF PREECLAMPSIA AND ECLAMPSIA COMPLICATIONS DURING PREGNANCY - Yuldasheva Barnokhonim; Dr. Aziza Forxodovna Rakhmatullayeva (Scholar Express Journals, 2025)
This article analyzes the perinatal outcomes of preeclampsia and eclampsia during pregnancy. Based on randomized clinical trials, retrospective and prospective studies, the impact on maternal and neonatal health was evaluated. The findings demonstrated significantly higher rates of preterm birth, low birth weight (LBW), low Apgar scores, neonatal intensive care unit (NICU) admissions, and perinatal mortality. The risk was particularly increased in cases of early-onset preeclampsia and in pregnancies complicated with HELLP syndrome
Keywords: preeclampsia; eclampsia; perinatal outcomes